Acute effects of different types of aerobic exercise on endothelial function and arterial stiffness. (29th August 2020) - Siasos, Gerasimos; Athanasiou, Dimitrios; Terzis, Gerasimos; Stasinaki, Aggeliki; Oikonomou, Evangelos; Tsitkanou, Stavroula; Kolokytha, Theodora; Spengos, Konstantinos; Papavassiliou, Athanasios G; Tousoulis, Dimitris
Abstract: Background: Chronic aerobic exercise training is associated with improved endothelial function and arterial stiffness and favourable long-term cardiovascular effects. Design: We investigated the acute effects of continuous moderate intensity aerobic exercise (CAE) and high intensity interval aerobic exercise (hIAE) on endothelial function and arterial stiffness in healthy participants. Methods: Twenty healthy men were recruited to this cross-over study. They participated in two exercise sessions: (a) CAE, volume at 50% of maximum aerobic work for 30 minutes; and (b) hIAE, interval maximum aerobic work for 30 minutes. Endothelial function was evaluated by flow-mediated dilation in the brachial artery. The carotid femoral pulse wave velocity and the femoral dorsalis pedis pulse wave velocity were measured as indices of central aortic and peripheral arterial stiffness. Measurements were carried out before and immediately after each exercise session. Results: There was no statistically significant difference in the baseline measurements before CAE and hIAE with respect to flow-mediated dilation, the carotid femoral pulse wave velocity and the femoral dorsalis pedis pulse wave velocity ( p = NS). Both CAE and hIAE significantly improved the flow-mediated dilation compared with baseline ( p < 0.001). Similarly, the femoral dorsalis pedis pulse wave velocity was improved after CAE and hIAE ( p < 0.005), whereas the carotid femoral pulse wave velocity was not significantly affected ( p = NS). Conclusion: Both CAE and hIAE can favourably affect endothelial function, suggesting another cardioprotective effect of acute exercise. These types of aerobic exercise have a different impact on the central and peripheral arterial stiffness.